Assessment of the existing multi-hazard methods: intended for monitoring natural threats on archaeological sites - Papageorgiou, Nikoletta; Hadjimitsis, Diofantos G.; Themistocleous, Kyriacos (My University, 2019)
Many archaeological sites and monuments of the world are at risk of natural disasters and potentially devastating natural events such as landsides, flood, fires and earthquakes, and effective risk reduction is only possible if all relevant threats are considered and analyzed. As opposed to single-hazard analyses, the examination of multiple hazards poses a range of additional challenges due to the differing characteristics of procedures. This refers to the evaluation of the hazard level, as well as to the vulnerability toward distinct processes, and to the arising risk level. As comparability of the single-hazard results is strongly required, an equivalent methodology has to be chosen that allows to estimate the overall hazard and subsequent risk level additionally to rank threats. The purpose of this paper is to provide a literature review of the two existing multi-hazards methods: Analytical Hierarchy process (AHP), and MmhRisk-HI (Model for multi-hazard Risk assessment with a consideration of Hazard Interaction) which used for several applications. A critical assessment of existing methods provides the opportunity to retrieve the main advantages and disadvantages of method. Furthermore, based on this critical assessment some of the methods will be implemented in different archaeological sites in Cyprus. Finally, the main attempt of the paper is to raise awareness on the benefits of advancements in EO technologies and of deriving products can bring to a more complete analysis and monitor natural threats on archaeological sites.
Keywords: Archaeological sites; EO technologies; Multi-hazards; Natural hazards; Risk; Single-hazard analysis